Subordinasi Tokoh Perempuan dalam Novel Kenanga Karya Oka Rusmini : Kajian Feminisme Liberal - Elvira Sirenden; Juanda Juanda; Hajrah Hajrah (Indonesian Journal of Social and Educational Studies, 2022)
Abstract: The Subordination of Female Characters in Oka Rusmini's Kenanga Novel: A Study of Liberal Feminism. Department of Indonesian Language and Literature, Faculty of Language and Literature. Makassar State University (supervised by Dr. Juanda, M.Hum and Dr. Hajrah, S.S., M.Pd.). This study aims to describe the subordination experienced by female characters in the novel Kenanga by Oka Rusmini. This research is descriptive qualitative. The data source in this study is the novel Kenanga by Oka Rusmini published by Grasindo in 2017 with a thickness of 273 pages. The data of this research are in the form of words, phrases, sentences and paragraphs that show the subordination and forms of resistance of female characters in the novel Kenanga by Oka Rusmini. The approach used in data analysis is Naomi Wolf's Libral Feminism theory. The results of this study indicate that First, the subordination experienced by female characters causes them to be in an unfavorable position, both in the personal, public, educational and social shutters. Second, the resistance of female characters in the novel Kenanga is shown by opposing the acts of subordination carried out by the patriarchy. Keywords: Liberal Feminism, Subordination, Resistance